Incorporation of RG1 epitope into HPV16L1-VLP does not compromise L1-specific immunity. Issue 27 (12th June 2019) - Schellenbacher, C.; Huber, B.; Skoll, M.; Shafti-Keramat, S.; Roden, R.B.S.; Kirnbauer, R.
Abstract: The candidate pan-Human Papillomavirus (HPV) vaccine RG1-VLP are HPV16 major capsid protein L1 virus-like-particles (VLP) comprising a type-common epitope of HPV16 minor capsid protein L2 (RG1; aa17-36). Vaccinations have previously demonstrated efficacy against genital high-risk (hr), low-risk (lr) and cutaneous HPV. To compare RG1-VLP to licensed vaccines, rabbits (n = 3) were immunized thrice with 1 µg, 5 µg, 25 µg, or 125 µg of RG1-VLP or a 1/4 dose of Cervarix®. 5 µg of RG1-VLP or 16L1-VLP (Cervarix) induced comparable HPV16 capsid-reactive and neutralizing antibodies titers (62, 500/12, 500–62, 500 or 1000/10, 000). 25 µg RG1-VLP induced robust cross-neutralization titers (50–1000) against hrHPV18/31/33/45/52/58/26/70. To mimic reduced immunization schedules in adolescents, mice (n = 10) were immunized twice with RG1-VLP (5 µg) plus 18L1-VLP (5 µg). HPV16 neutralization (titers of 10, 000) similar to Cervarix and Gardasil and cross-protection against hrHPV58 vaginal challenge was observed. RG1-VLP vaccination induces hrHPV16 neutralization comparable to similar doses of licensed vaccines, plus cross-neutralization to heterologous hrHPV even when combined with HPV18L1-VLP.